(untitled) (Research, Society and Development, 2020)
The demand for energy and the pressure for reducing environmental impacts is increasing in developing countries, mainly in agricultural areas. The generation of electricity from photovoltaic panels can be economically and environmentally advantageous as a source of renewable energy and the ability to reach remote consumers. The present study aimed to evaluate the performance of a photovoltaic system equipped with a sun-tracking device, comparing to a fixed panel. The test compared two panels of a photovoltaic cell system, one used a rotation module in two-axis, and the other a fixed one (control), for capturing solar energy throughout the day in a tropical region of Brazil. Solar energy data were obtained in the two photovoltaic panels with data continuously recorded six months, with a weather characteristic of high cloudiness and rainfall indexes. The commissioning of the tested photovoltaic panels was done on bright days. Power results indicated that the two-axis tracker system was useful during the test, presenting an increase of 26% when compared to the fixed panel. It was found that when the cloudiness and the rain index are very high, the sun tracking system might not be as efficient as foreseen. Rainfall and cloudiness index are essential factors for determining the feasibility of using a tracker device in tropical regions.